"That's the Weight of Knowing": Practitioner Skills and Impact When Delivering Psychoeducational Group Work for Women Who Have Experienced IPV. Issue 4 (1st October 2016) - Morton, Sarah; Hohman, Melinda
ABSTRACT: Few studies have examined the psychosocial impact on practitioners when carrying out group work with clients who are survivors of intimate partner violence (IPV), substance use, and childhood abuse. This article begins with a review of the literature on social and psychosocial problems associated with women who experience IPV, types of group interventions with this client group, and the impact that this work may have on practitioners. It then describes the use of an action research method of inquiry groups involving six facilitators at an agency in Ireland. Three themes emerged from the analysis of transcripts drawn from four group interviews: conscious collaboration, reflections on professional expertise and life experience, and attention to safety. The findings suggest that building collaborative relationships with group participants is a complex, skilled process and that the worldviews of facilitators were strongly affected. The article concludes with a discussion about implications for practice.